GhKWL1 Upregulates GhERF105 but Its Function Is Impaired by Binding with VdISC1, a Pathogenic Effector of Verticillium dahliae - Chen, Yang (Int J Mol Sci, 2021)
Verticillium wilt, caused by Verticillium dahliae, is a devastating disease for many important crops, including cotton. Kiwellins (KWLs), a group of cysteine-rich proteins synthesized in many plants, have been shown to be involved in response to various phytopathogens. To evaluate genes for their function in resistance to Verticillium wilt, we investigated KWL homologs in cotton. Thirty-five KWL genes (GhKWLs) were identified from the genome of upland cotton (Gossypium hirsutum). Among them, GhKWL1 was shown to be localized in nucleus and cytosol, and its gene expression is induced by the infection of V. dahliae. We revealed that GhKWL1 was a positive regulator of GhERF105. Silencing of GhKWL1 resulted in a decrease, whereas overexpression led to an increase in resistance of transgenic plants to Verticillium wilt. Interestingly, through binding to GhKWL1, the pathogenic effector protein VdISC1 produced by V. dahliae could impair the defense response mediated by GhKWL1. Therefore, our study suggests there is a GhKWL1-mediated defense response in cotton, which can be hijacked by V. dahliae through the interaction of VdISC1 with GhKWL1.